Implementation in a Family Medicine Clinic of a Lifestyle Program Designed to Help Indigent, Obese Adult Patients Lose Weight - Harvey, Anne T.; Lewis, Douglas P.; Duggins, Maurice L. (Kansas Journal of Medicine, 2016)
Introduction. Efficacy of interventions in research settings maynot translate to usual-care settings. The impact of interventionsvaries depending upon factors, such as the proportion andcomposition of the population reached and engaged, as well asparticipation and implementation characteristics of providers.Methods. A lifestyle intervention meant to achieve a 5%loss of body weight in six months was offered to obese, indigentadult patients in a Family Medicine residency outpatientclinic. Implementation variables were assessed, includingdetermination of individual patient penetrationand participation rate, demographic representativeness,completion rate, outcomes, and differential impact, as wellas setting participation rates and implementation fidelity.Results. From a population of 743 potentially eligible patients,356 were invited to participate (48% penetration) and158 were enrolled (44% participation). Those enrolled wereheavier (BMI of 42.6 vs 39.0), younger (43.5 vs 47.0 years)and more likely female (87% vs 69%) than those not enrolled.Individual completion rate was 81%; overall weightloss was negligible. Setting participation was broad, butfidelity to background standard of care was only 50%.Conclusions. Providers were eager for a tool to help their obese,indigent patients lose weight, but the intervention proved ineffectiveand the usual care of enrolled patients was not stronglysupportive of their weight loss efforts. KS J Med 2016;9(4):77-82.